2004
DOI: 10.1002/eji.200324463
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II‐independent CD25+ CD4+ CD8α β+ α β T cells attenuate CD4+ T cell‐induced transfer colitis

Abstract: CD4 + § g T cell populations that develop in mice deficient in MHC class II (through 'knockout' of either the A § , or the A g chain of the I-A b molecule) comprise a major 'single-positive' (SP) CD4 + CD8 -subset (60-90%) and a minor 'double-positive' (DP) CD4 + CD8 § g + subset (10-40%). Many DP T cells found in spleen, mesenteric lymph nodes (MLN) and colonic lamina propria (cLP) express CD25, CD103 and Foxp3. Adoptive transfer of SP but not DP T cells from A § -/-or A g -/-B6 mice into congenic RAG -/-host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Treg differentiation requires TCR interactions with MHC-II molecules (ref. 10 and references therein), as engagement of the TCR by agonist ligands during thymic differentiation strongly favors clonal deviation into the FoxP3+ lineage, either by inducing differentiation along the lineage (11) or because FoxP3+ cells are inherently more resistant to clonal deletion (12). Accordingly, the analysis of mice expressing a Nurr77-GFP reporter, whose expression correlates with the strength of cell activation via the TCR, showed that the reporter was generally expressed at a higher level in Treg than in Tconv cells (13).…”
Section: Imbalanced Signal Transduction In Regulatory T Cells Expressmentioning
confidence: 99%
“…Treg differentiation requires TCR interactions with MHC-II molecules (ref. 10 and references therein), as engagement of the TCR by agonist ligands during thymic differentiation strongly favors clonal deviation into the FoxP3+ lineage, either by inducing differentiation along the lineage (11) or because FoxP3+ cells are inherently more resistant to clonal deletion (12). Accordingly, the analysis of mice expressing a Nurr77-GFP reporter, whose expression correlates with the strength of cell activation via the TCR, showed that the reporter was generally expressed at a higher level in Treg than in Tconv cells (13).…”
Section: Imbalanced Signal Transduction In Regulatory T Cells Expressmentioning
confidence: 99%
“…Furthermore, the periphery of MHC II Ϫ/Ϫ mice contains CD8 ϩ CD25 ϩ T cells that exhibit contact-dependent suppressive activity analogous to that mediated by wild-type CD4 ϩ CD25 ϩ T cells (20). Other reports have indicated that a unique subset of CD4 ϩ CD8 ϩ CD25 ϩ T cells in MHC II Ϫ/Ϫ mice is enriched in FoxP3 mRNA and capable of suppressing T cellmediated inflammatory bowel disease (21). Curiously, while prevalent in MHC II Ϫ/Ϫ mice, CD8 ϩ CD25 ϩ T cells are quite rare in wild-type animals (20).…”
Section: Foxp3mentioning
confidence: 99%
“…18 eGFP-tg B6 mice express eGFP under the chicken ␤-actin promoter control. 17 eGFP is heterogeneously expressed from the transgene in the CD4 ϩ T-cell population of transgenic mice but remains stable within the adoptive host.…”
Section: Isolation and Adoptive Transfer Of Gfp ϩ Cd4mentioning
confidence: 99%
“…Twelve l of RNA isolated from microdissected tissue or 1 l of RNA prepared from cell suspensions, respectively, were annealed to 1 pmol of hexamer (random) primer, denatured at 80°C and reverse-transcribed as described. 18 Real-Time PCR mRNA expression was determined by real-time reverse transcriptase (RT)-PCR and relative quantification using the reference gene HPRT or CD3, respectively. Primers for HPRT and Foxp3 were as published elsewhere.…”
Section: Rna Isolation and Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation